Investigating the influence of distributed leadership on school effectiveness: a mediating role of teachers' commitment - Mohd Ali, Hairuddin; Yangaiya, Salisu Abba (Mediterranean Center of Social and Educational Research, 2015)
The purpose of this study is to investigate the influence of distributed leadership (DL) on school effectiveness (SE) in junior secondary schools in Katsina state, Nigeria. The study also investigates if teachers’ commitment (TC) mediates the relationship between DL and SE. The study sampled three hundred and one (301) teachers. SPSS version (16.0) and Analysis of Moment Structure (AMOS) version (16.0) were used to analyze the data collected. The results indicated that there is a statistically significant relationship between DL and SE (with standardized coefficient .68). In addition, TC influences SE (with standardized coefficient 0.38). Moreover, TC mediates the relationship between DL and SE (standardized coefficient 0.22). The implication of the study is that all stake holders; head teachers, zonal office staff, ministry officials among others are now better informed about the mediating role of TC on DL and SE. The results contributes to the existing body of knowledge in Nigeria. Very few studies investigate the relationship between DL and SE, in Katsina state in particular, and Nigeria in general.